THE RADIAL DISTRIBUTION OF IMPLANTED AND TRAPPED 4HE IN SINGLE DIAMOND CRYSTALS AND IMPLICATIONS FOR THE ORIGIN OF CARBONADO - Shelkov D.A.; Verchovsky A.B.; Milledge H.J.; Pillinger C.T. (My University, 1998)
We have investigated variations of 4He content in the different zones of single natural diamond crystals using a step combustion technique. The results indicate that some diamonds may be strongly irradiated during their residence in the earth's crust, since concentrations of 4He in the 30-μm outer layer were found to be as high as 0.014 cm3/g. The observation leads to a conclusion that similarly high 4He concentrations in carbonado diamonds do not necessary demand an exotic origin. Previous theoretical estimations of the magnitude of He implantation in diamonds, which use normal U-Th concentrations of ca. 30 ppm in the surrounding rocks, do not agree with experimentally-obtained results. The He concentrations actually found in the `skins' (outer ~30- μm layer of the crystals) of the samples we studied, require concentrations of U and Th in the host rock from 160 ppm to 1000 ppm. The interiors of the samples have also been analysed and exhibited 4He concentrations from 3x10-7 cm3/g to 2x10-5 cm3/g, indicating heterogeneity even within single diamond crystals and arguing for the changes in the growth environment. From 4He zoning within a diamond from the Finsch kimberlite, a maximum 4He diffusion coefficient was estimated to be ~4x10-21 cm2/s, lower than previous estimates, indicating that diamond may retain indigenous 4He in the structure during its residence under mantle PT conditions.
Keywords: DIAMOND; HELIUM; CARBONADO; IMPLANTATION; DIFFUSION